Tourist Tales: Eco-tourism and Orangutans - Russell, Constance (UnderCurrents: Journal of Critical Environmental Studies, 1993)
In my own "tour of desire," I travelled in the Fall of 1992 to see the orangutans of Borneo. On a personal level, I had wanted to see orangutans in the wild ever since studying them in the zoo a number of years ago for my B.A. thesis. At the time, I was a psychology major specializing in animal behaviour, and had elected to do an observational study on sex differences in their play behaviour. I spent many hours watching these magnificent creatures, so like us, confined to such maddeningly small and barren quarters, and I longed to see them as they ought to be: in their own world, in context. But I also went as a researcher to document and analyze the other tourists’ reactions to, and experiences with, the orangutans. [...]